Trend Analysis of Historical Drought During 1929-2016 in Diyarbakır Station with Innovative Şen Method - Veysel Gümüş; Latif Doğan Dinsever; Oğuz Şimşek (Doğal Afetler ve Çevre Dergisi)
Drought, a natural disaster, affects various sectors such as water supply, hydropower generation, agriculture, and industry. It is important to determine temporal change of drought in order to use water resources effectively and efficiently. In this study, drought analysis is performed using monthly total precipitation data measured between 1929-2016 at the meteorology observation station in Diyarbakır, Turkey. A homogeneity test is also made before drought analysis. The Standardized Precipitation Index (SPI) method is used to determine drought for 1, 3, 6 and 12 months’ time scales, and Innovative Şen Method (also known as Innovative Trend Analysis-ITA) is used to identify the trend of drought indices values for different time scales. The driest periods are determined according to time scales of 1, 3, 6 and 12 months are found as 8, 18, 21 and 53 months, respectively. While the percentage of dry periods is 40% for the 1-month time scale (SPI-1), and about 50% for the other time scales. The percentage of droughts (sum of moderate, severe, and extreme drought) for 3-months (SPI-3), 6-months (SPI-6) and 12-months (SPI-12) is between 15% and 16.5%. The ITA method results show that a weak decreasing trend found on SPI-12 for indices value greater than 0.8, and a strong decreasing trend (more than 5%) is calculated for moderate wet values. In addition, it is determined that the index values, less than -3 and -3, in SPI-12 values shows a very strong increasing trend (more than 10%). Its means that the extreme dry situation has decreased in recent years.